2013
DOI: 10.1182/blood-2013-04-491753
|View full text |Cite
|
Sign up to set email alerts
|

To shrink or not to shrink

Abstract: These data also raise the question of how best to target anergy in CLL. One intriguing possibility is combination with other targeted CLL therapies. Currently, much attention is focused on the treatment of CLL with inhibitors of the BCR signaling pathway, especially the phosphatidylinositol3-kinase inhibitor GS-1101 and the Bruton tyrosine kinase inhibitor ibrutinib. Preliminary data with ibrutinib suggest that patients with IgVH-unmutated disease, associated with more active BCR signaling, respond earlier tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It has been suggested that Piezo1 plays a previously unrecognized role in erythrocyte volume regulation, with HX erythrocytes gradually becoming dehydrated during repeated cycles of travel through the microcirculation, associated with changes in oxygenation/deoxygenation (34). A potential role in regulating a stretch-activated calcium pathway has also been suggested (35)(36)(37)(38).…”
Section: Piezo1 In Erythrocytesmentioning
confidence: 99%
“…It has been suggested that Piezo1 plays a previously unrecognized role in erythrocyte volume regulation, with HX erythrocytes gradually becoming dehydrated during repeated cycles of travel through the microcirculation, associated with changes in oxygenation/deoxygenation (34). A potential role in regulating a stretch-activated calcium pathway has also been suggested (35)(36)(37)(38).…”
Section: Piezo1 In Erythrocytesmentioning
confidence: 99%
“…It has been suggested that PIEZO1 plays a role in erythrocyte volume regulation, with PIEZO1-mutant HX erythrocytes gradually becoming dehydrated during their repeated cycles of travel through the microcirculation, associated with changes in oxygenation/deoxygenation. 35 Genetic and physiologic studies implicate a role for PIEZO1 in volume homeostasis. Volume sensing, a poorly understood process in vertebrate cells, has been linked to stretchactivated currents induced by changes in cell volume.…”
Section: Piezo1 and Erythrocyte Volumementioning
confidence: 99%
“…59 It has been suggested that PIEZO plays a role in erythrocyte volume regulation, 60 with PIEZO1-mutant HX erythrocytes gradually becoming dehydrated during their repeated cycles of travel through the microcirculation, associated with changes in oxygenation/deoxygenation. 61 Volume sensing, a poorly understood process in vertebrate cells, has been linked to stretch-activated currents induced by changes in cell volume. 62 The PIEZO1 blocker, Grammostola spatulata mechanotoxin, inhibits mechanically activated currents and whole cell regulatory volume decreases, indicating a role in volume homeostasis.…”
Section: Dehydrationmentioning
confidence: 99%